Problems and Solutions. Issue 1 (31st December 2021) - Ullman, Daniel H.; Velleman, Daniel J.; Wagon, Stan; West, Douglas B.; ,
Abstract : Proposed problems, solutions, and classics should be submitted online at americanmathematicalmonthly.submittable.com/submit. Proposed solutions to the problems below must be submitted by May 31, 2022. More detailed instructions are available online. Proposed problems must not be under consideration concurrently at any other journal nor be posted to the internet before the deadline date for solutions. This month, we introduce a new subsection of Problems and Solutions called Classics, which appears at the end of the section.